2019
DOI: 10.1002/ags3.12237
|View full text |Cite
|
Sign up to set email alerts
|

Role of nutrition in gastroenterological surgery

Abstract: Nutrition plays important roles in recovery after gastroenterological surgery. Severe surgical stress increases muscle breakdown and lipolysis, thereby accelerating wound healing and enhancing host defense against microbes. Malnourished patients have insufficient amounts of muscle and body fat. Therefore, they may not appropriately respond to surgical stress. Perioperative nutritional therapy maintaining nutritional status reduces postoperative complications and accelerates recovery after surgery, particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 41 publications
0
41
0
1
Order By: Relevance
“…It was reported that perioperative IN significantly reduced the risk of postoperative infectious complications by 50% [37]. It should be emphasized that, although WHO and Centers for Disease Control and Prevention guidelines for the prevention of surgical site infection did not refer to the significance of nutrition therapy in previous versions, the 2016 WHO guidelines listed IN as a method contributing to the prevention of surgical site infection [38].…”
Section: Immunomodulating Mechanisms Of Nutrients Used In Inmentioning
confidence: 99%
See 4 more Smart Citations
“…It was reported that perioperative IN significantly reduced the risk of postoperative infectious complications by 50% [37]. It should be emphasized that, although WHO and Centers for Disease Control and Prevention guidelines for the prevention of surgical site infection did not refer to the significance of nutrition therapy in previous versions, the 2016 WHO guidelines listed IN as a method contributing to the prevention of surgical site infection [38].…”
Section: Immunomodulating Mechanisms Of Nutrients Used In Inmentioning
confidence: 99%
“…The route of IN is also very important because it influences the host defense mechanism. Comparing enteral and parenteral routes, enteral nutrition (EN) is better than total parenteral nutrition (TPN) [37]. EN preserves and TPN reduces gut-associated lymphoid tissue cell number, gut immunoglobulin A (IgA) level, respiratory tract IgA level, hepatic mononuclear cell number, resident macrophage number, and exudative neutrophil number [37].…”
Section: Immunomodulating Mechanisms Of Nutrients Used In Inmentioning
confidence: 99%
See 3 more Smart Citations